The Virgin and her Lover : Fragments of an Ancient Greek Novel and a Persian Epic Poem - Utas, Bo, (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
Starting from the authors' discovery that the Persian epic poem Vāmiq and ʿAdhrā by ʿUnṣurī (11th century AD) derives from the ancient Greek novel of Mētiokhos and Parthenopē, the book contains critical editions of the Greek and Persian fragments and testimonia, with English translation and comments. The exciting story of the modern recovery of the two texts is told, and the transformations of the productive theme of The ardent lover and the virgin are traced from Greek novel to Persian poem, and through later Persian and Turkish literature. Of particular importance is the authors' attempt to reconstruct the common plot and individual variations, adding a new work to the limited corpus of ancient novels and shedding new light on the genre of Persian epic poetry.